Status Keberlanjutan Usaha Pembibitan Itik Talang Benih (Anas Platyrhynchos) Sebagai Plasma Nutfah Provinsi Bengkulu - Handayani, Eny; Romdhon, M. Mustopa; Santoso, Urip; Fenita, Yosi; Badarina, Irma (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
Talang Benih Duck (anas platyrhynchos) is the germplasm of Bengkulu province. The population at the UPTD of Livestock Breeding and Animal Feed, the Livestock and Animal Health Service of Bengkulu Province tends to decrease (quantity and quality), so it is necessary to study the status of sustainability so that its sustainability is maintained. This study aims to identify sensitive attributes of environmental factors that determine the sustainability status of the Talang Benih duck breeding business based on sustainable germplasm. Sustainability analysis was carried out using the Multidimensional Scaling (MDS) analysis method. The results of the leverage analysis show that there are 46 sensitive attributes and the Monte Carlo analysis shows a stress value of 17,40% and a coefficient of determination (R2) of 92,80%. The results showed that the status of sustainability was less sustainable (46,56) with less sustainable ecological dimensions (49,61), less sustainable economic dimensions (46,20), quite sustainable technological dimensions (62,66), less sustainable social dimensions (31,03), as well as legal and institutional dimensions that are less sustainable (43,32).   Keywords : Multidimensional scaling, sustainability status, Talang Benih ducks